Gaze communicates both cue direction and agent mental states - Mayrand, Florence; Capozzi, Francesca; Ristic, Jelena (Frontiers in Psychology, 2024)
Although it is well established that humans spontaneously attend to where others are looking, it remains debated whether this gaze following behavior occurs because gaze communicates directional information (i.e., where an agent is looking) or because gaze communicates an agent's inferred mental content (i.e., what an agent perceives), both of which rely on the processes involved in the general Theory of Mind ability. To address this question, in two Experiments we used a novel task to measure how spatially dissociated and spatially combined effects of an agent's gaze direction and perceived mental content influence target performance. We also contrasted performance for social directional cues and nonsocial arrows. Our data revealed that performance was compromised when cue direction and mental content dissociated relative to when they combined. Performance for dissociated components was especially prominent when a social avatar served as a cue relative to a comparison arrow. Together, these data show that a typical gaze signal communicates information about both where an agent is attending and what they are attending to.